Comparison of clinical outcomes between catheter ablation and permanent pacemaker implantation in Tachycardia-Bradycardia Syndrome patients: a meta-analysis - Sunu Budhi Raharjo; Emir Yonas; Sarah Naura Irbah; Dicky Armein Hanafy; Muhammad Rizky Felani; Aldo Ferly; Fa Po Chung (International Journal of Cardiology: Heart & Vasculature)
Introduction: Tachycardia-Bradycardia Syndrome (TBS) is a clinical disorder resulting from complications associated with sick sinus syndrome (SSS). In patients with SSS, TBS is marked by alternating episodes of tachycardia and bradycardia. This meta-analysis aims to evaluate and compare the differences in clinical outcomes between ablation and pacemaker treatments for TBS. Methods: We performed a systematic search on libraries, including PubMed, EuropePMC, SCOPUS, Cochrane Central, and medRxiv, for preprint studies. The search terms used were “Tachycardia Bradycardia Syndrome,” “Pacing,” and “Ablation” between the pacing and ablation groups in TBS patients. Review Manager Software Version 5.4 (Cochrane Collaboration) was used to perform the meta-analysis. Results: We identified 1,138 potential articles from our search, and 521 duplicates were removed. After screening the titles and abstracts of the remaining 662 articles, we obtained 23 potentially relevant articles. Finally, we included the remaining eight studies in our qualitative synthesis and meta-analysis, which comprised 1,266 patients.Catheter ablation was associated with a lower incidence of AF recurrence (OR of 0.09 [0.04, 0.22; p < 0.001], with moderate heterogeneity (I2 = 76 %, p < 0.001), stroke (OR of 0.28 [0.14, 0.53; p < 0.001] low heterogeneity I2 = 0 %, p = 0.99 favouring the ablation group.) and lower mortality (OR of 0.37 [0.17, 0.80; p0.01] low heterogeneity I2 = 0 %, p = 0.84 favouring the ablation group), compared to those who underwent pacemaker implantation in patients with TBS. Conclusion: Catheter ablation resulted in a lower incidence of AF recurrence, stroke, and mortality compared to the pacemaker in TBS patients. There was no difference between groups regarding procedure-related complications and cardiovascular rehospitalization.